BUDAYA KERJA ISLAMI GURU-GURU SDN KOTA SOLOK DALAM MENINGKATKAN MUTU HASIL BELAJAR - Yemfimer Rahmi (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Work Culture Islamic Teachers of SDN Solok In Improving the Quality of Learning Outcomes. The study was conducted using a qualitative research approach with the types of qualitative research focus is to describe, analyze and interpret cultural groups. SDN object of this paper is ranked by the Solok, 06 Cape Nails SDN, SDN 16 and SDN Nan Balimo 15 Soil Salts, owns the speci schools provide educational services using principles of sharia.From the research that has been done, the Data Showed that at SDN 06 and SDN Tanjung Paku 15 Nan culture Balimo implementation work has been going well and is supported by the parents, while at SDN 16 Soil Salts implementation work culture has also been applied by the teacher but not yet Implemented perfectly Because parental background factors and are not supported by the parents.From the findings of the research, educational services become very important to the school as education. With services unit thus spake not only the nature of educational services related to meeting the needs of infrastructure, equipment and tools paced learning luxurious and sophisticated, but much needed school climate and environment / learning conducive, safe, and fun.Kata Kunci:  Budaya Kerja, guru-guru, mutu hasil belajar